2015
DOI: 10.1523/jneurosci.5227-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Supplementation Attenuates Cocaine-Seeking Behaviors and Cocaine-Induced c-Fos Activation in a DNA Methylation-Dependent Manner

Abstract: Epigenetic mechanisms, such as histone modifications, regulate responsiveness to drugs of abuse, such as cocaine, but relatively little is known about the regulation of addictive-like behaviors by DNA methylation. To investigate the influence of DNA methylation on the locomotor-activating effects of cocaine and on drug-seeking behavior, rats receiving methyl supplementation via chronic L-methionine (MET) underwent either a sensitization regimen of intermittent cocaine injections or intravenous self-administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 78 publications
11
89
0
Order By: Relevance
“…Though initially thought to determine the setting of hedonic tone, the functions of dopaminergic circuitry are now understood to be more intricate, coding for attention, reward expectancy, disconfirmation of reward expectancy, and incentive motivation. Elevated stress levels, along with dopaminergic gene polymorphisms and additional neurotransmitter genetic variants, may have an aggregate effect on the susceptibility to both food and drug addictions involving epigenetic effects (Wright et al., 2015). Recently, Badgaiyan, Sinha, Sajjad, and Wack (2015) clearly showed that dopaminergic tone at rest is reduced in attention-deficit/hyperactivity disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Though initially thought to determine the setting of hedonic tone, the functions of dopaminergic circuitry are now understood to be more intricate, coding for attention, reward expectancy, disconfirmation of reward expectancy, and incentive motivation. Elevated stress levels, along with dopaminergic gene polymorphisms and additional neurotransmitter genetic variants, may have an aggregate effect on the susceptibility to both food and drug addictions involving epigenetic effects (Wright et al., 2015). Recently, Badgaiyan, Sinha, Sajjad, and Wack (2015) clearly showed that dopaminergic tone at rest is reduced in attention-deficit/hyperactivity disorder.…”
Section: Discussionmentioning
confidence: 99%
“…), immediately before being placed in the operant conditioning chambers for the drug-primed reinstatement sessions. This dose of ketamine equates to the therapeutic range previously used to assess antidepressant-like effects of ketamine (Carrier and Kabbaj 2013), and the dose of cocaine has been used previously to trigger cocaine-seeking behaviors after daily self-administration and extinction (Wright et al 2015). …”
Section: Methodsmentioning
confidence: 99%
“…All METH-trained rats significantly escalated their intake of the drug per session during the first 16 days and then maintained their intake for the remainder of the training session (Figure 1b). The repeated measures mixed analysis of variance for rewards earned included the between-subject factor group (control (CT), shocksensitive (SS), shock-resistant (SR)) and the within-subject factor of day (training days [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. This analysis showed a significant effect of day × group (F (38, 608) = 18.4, P o0.001).…”
Section: Statistical Analysesmentioning
confidence: 97%
“…[1][2][3] Behavioral phenomena observed during drug SA are regulated by a diversity of interconnected but distinct brain regions that include the nucleus accumbens (NAc) and dorsal striatum, among others. [4][5][6] The NAc is an important link in the circuit of addiction because it connects to brain regions that subsume positive memory 7 and decision making, 8 two cognitive processes that regulate drug-taking behaviors in rodents and humans.…”
Section: Introductionmentioning
confidence: 99%